Discounts and their effects: Economic and legal approach - Rastislav Funta (DANUBE: Law, Economics and Social Issues Review, 2014)
The present article discusses the economic and legal effects of single-product loyalty discounts. It is clear that arguments concerning the "pro-competitive" effects of such discounts must be judged with skepticism. This applies in particular to the assumed effects of loyalty discounts resulting from double profit surcharges or falling average costs, as well as in the context of price discrimination. I argue that many of the alleged effects could also be achieved with discount forms where the risk of restrictive effects on competition should be lower. Also, the assumed anti-competitive effects of loyalty discounts must be better justified economically. This article suggests using a form-based approach for the assessment of discount schemes. However, this should not amount to a restrictive assessment of certain discount schemes. For the development of such a form-based approach, it is necessary to review the theories about pro-competitive and anti-competitive effects. Therefore, this article attempts to identify which positive effects are more likely to be achieved by means of which discount forms and under which circumstances.
Keywords: 330; Discounts; Economies of Scale; Predatory Competition; Pro-competitive Effects